Amorphous Molybdenum Selenide Nanosheet as an Efficient Trap for the Permanent Sequestration of Vapor‐Phase Elemental Mercury. Issue 20 (14th August 2019) - Yang, Zequn; Li, Hailong; Yang, Junwei; Yang, Qin; Zhao, Jiexia; Yang, Jianping; Qu, Wenqi; Feng, Yong; Shih, Kaimin
Abstract: The key challenge of vapor‐phase elemental mercury (Hg 0 ) sequestration is the rational design of a sorbent with abundantly available ligands that exhibit excellent affinity toward Hg 0 to simultaneously achieve a high uptake capacity and rapid capture rate. In this work, it is demonstrated how the correct combination of functional ligands and structural properties can form an ideal remediator for permanent Hg 0 immobilization. The adsorption capacity of an amorphous molybdenum triselenide (MoSe3 ) nanosheet greater than 1000 mg g −1 is the highest recorded value compared to previously reported sorbents tested in a fixed‐bed reactor. Meanwhile, the uptake rate of 240 µg g −1 min −1 is also the highest recorded rate value. Mercury selenide as formed exhibits extremely low leachability when environmentally exposed. This impressive performance is primarily attributed to the appropriate layer space between the nanosheets that permeated Hg 0 and the existence of diselenide (Se2 2− ) ligands that exhibit excellent affinity toward Hg 0 . Thus, this work not only provides a promising trap for permanent Hg 0 sequestration from industrial and domestic sources with minimum hazard but also provides a detailed illustration of using structural advantages to obtain an ideal sorbent as well as guidance for the further development of Hg 0 decontamination techniques. Abstract : An amorphous molybdenum selenide (MoSe3 ) sorbent is developed for efficient and permanent vapor‐phase elemental mercury (Hg 0 ) sequestration. After the rational design, the MoSe3 with increased interlayer space and abundant diselenide ligands shows the highest recorded performance for Hg 0 capture. This work provides a new mindset for engineering a Hg 0 trap using the appropriate combination of functional groups and structural properties.